Atrioventricular Block as the Initial Manifestation of Cardiac Sarcoidosis in Middle-Aged Adults - NERY, PABLO B.; BEANLANDS, ROB S.; NAIR, GIRISH M.; GREEN, MARTIN; YANG, JIM; MCARDLE, BRIAN A.; DAVIS, DARRYL; OHIRA, HIROSHI; GOLLOB, MICHAEL H.; LEUNG, EUGENE; HEALEY, JEFF S.; BIRNIE, DAVID H. (Journal of cardiovascular electrophysiology, 2014)
Cardiac Sarcoidosis Presenting as Atrioventricular Block Introduction Atrioventricular block (AVB) can be caused by several conditions, including cardiac sarcoidosis (CS). The prevalence of CS causing this presentation in a North American population has not been investigated and was the purpose of this study. Methods We prospectively evaluated patients aged 18–60 years presenting with unexplained 2nd or 3rd degree AVB and no previous history of sarcoidosis in any organ. All patients had fluorodeoxyglucose‐positron emission tomography (FDG‐PET) scans for the evaluation of CS. Japanese Ministry of Health Welfare (JMHW) criteria and biopsy results were used to confirm the diagnosis of CS. Subjects with advanced imaging suggestive of CS were investigated for extracardiac involvement. Patients were followed for major adverse cardiac events. Results Thirty‐two patients presenting with unexplained AVB underwent cardiac and whole body FDG‐PET for the investigation of CS from February 2010 to June 2013. Mean age was 52.8 ± 6.2 years, and 20 were male. CS was diagnosed in 11/32 (34%) subjects and 11/11 were subsequently diagnosed with extra‐CS. Average follow‐up was 21 ± 9 months. Adverse events were observed in 3 subjects with CS but none in subjects with idiopathic AVB. All 3 patients presented with heart failure, 2 also had recurrent VT resulting in ICD shocks. Conclusions In this prospective study of consecutive patients aged ≤60 years presenting with unexplained AVB, we found that 11/32 (34%) had previously undiagnosed CS. Among patients with CS, 3/11 had adverse clinical outcomes compared with 0/21 (P = 0.011). Our data suggest that all patients aged ≤60 years with unexplained AVB should be investigated for CS. Moreover, patients diagnosed with CS should be closely followed.